Notch Signaling is Associated with ALDH Activity and an Aggressive Metastatic Phenotype in Murine Osteosarcoma Cells - Mu, Xiaodong; Isaac, Christian; Greco, Nicholas; Huard, Johnny; Weiss, Kurt (Frontiers in Oncology, 2013)
Osteosarcoma (OS) is the most common primary malignancy of bone, and pulmonary metastatic disease accounts for nearly all mortality. However, little is known about the biochemical signaling alterations that drive the progression of metastatic disease. Two murine OS cell populations, K7M2 and K12, are clonally related but differ significantly in their metastatic phenotypes and therefore represent excellent tools for studying metastatic OS molecular biology. K7M2 cells are highly metastatic, whereas K12 cells display limited metastatic potential. Here we report that the expression of Notch genes (Notch1, 2, 4) are up-regulated, including downstream targets Hes1 and Stat3, in the highly metastatic K7M2 cells compared to the less metastatic K12 cells, indicating that the Notch signaling pathway is more active in K7M2 cells. We have previously described that K7M2 cells exhibit higher levels of aldehyde dehydrogenase (ALDH) activity. Here we report that K7M2 cell ALDH activity is reduced with Notch inhibition, suggesting that ALDH activity may be regulated in part by the Notch pathway. Notch signaling is also associated with increased resistance to oxidative stress, migration, invasion, and VEGF expression in vitro. However, Notch inhibition did not significantly alter K7M2 cell proliferation. In conclusion, we provide evidence that Notch signaling is associated with ALDH activity and increased metastatic behavior in OS cells. Both Notch and ALDH are putative molecular targets for the treatment and prevention of OS metastasis.